PENGAJARAN YOGA OLEH INSTRUKTUR LOMBOK YOGA CENTER SEBAGAI DAYA TARIK WISATA WELLNESS DI LOMBOK - Wayan Ayumita Astrina; Ida Kade Suparta; Dewi Kusumasanthi (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
Lombok Yoga Center is a local institution that plays a vital role in supporting the development of yoga as part of wellness tourism in Lombok, consistently sending yoga instructors to teach in various hotels and resorts. However, there are not many studies that specifically investigate the implementation of yoga training that is conducted. The purpose of this research is to deeply explore the practices, challenges, and strategies of the instructors at Lombok Yoga Center who teach tourists in hotels and resorts in Lombok. This research uses a qualitative approach by collecting data through non-participant observation, semi-structured interviews with 5 instructors from the Lombok Yoga Center, and documentation studies. Data analysis applies the Miles and Huberman model. The results of the study show that the yoga teaching practices by instructors at the Lombok Yoga Center are flexible and adaptive, adjusting to the backgrounds and needs of tourists. Several aspects considered challenges by the instructors include adjusting fees to tourists' expectations, cultural differences among tourists, and maintaining participants' attention during classes. To maintain the quality of the classes, instructors implement several strategies focusing on personal approach, communication, flexibility, and professionalism.